Integration of thin film bulk acoustic resonators onto flexible liquid crystal polymer substrates - Wright, Robert V.; Hakemi, Ghazal; Kirby, Paul B. (Elsevier Science B.V., Amsterdam., 2011)
Thin film bulk acoustic resonators (FBARs) have been directly integrated on liquid crystal polymer (LCP) substrates for application to the field of flexible electronics. Particular developments required were chemo-mechanical polishing for LCP roughness reduction to enable growth of high quality ZnO films and a through substrate deep reactive ion etch process. Q values of up to 126 and 78 for series and parallel resonances combined with an electromechanical coefficient ∼ 6.7% were achieved. Further device development is needed but this performance is already sufficient for some chemical/biological sensing applications.
Keywords: FBAR; Flexible electronics; LCP; RF MEMS